Características tomográficas da fissura petrotimpânica em pacientes portadores de zumbido - Moraes, Samuel De Souza [UNIFESP] (2019)
Objective: To determine the frequency of PTF types by temporal bones CT in tinnitus patients, and to study the relationship between PTF anatomy and tinnitus. Method: An observational, longitudinal and retrospective analytical study was performed between January 2010 and July 2017. Patients were selected who meet the following inclusion criteria: 1) to have tinnitus 2) performed CT of the temporal bones in Imaging Diagnostic Department (IDD) of the institution, 3) to have a minimum age of 18 years of both sexes. Patients who had the following tomographic changes were excluded from the sample: 1) presence of inflammatory disease of ear and osteodystrophies and / or malformations in the middle ear, 2) Changes in TC compatible with surgical intervention in the middle or inner ear, and 3) TC imaging compatible with degenerative disease in TMJ, and also the patients who took ototoxic medication in the last 3 months were excluded. These patients comprised the study group. The same number of patients was selected to compose the control group with the same criteria. TC were evaluated by three experienced professionals, and the Sato et al (2008) criteria was used. Were are performed measures of PTF lengths and the tomographics changes were scored. The avaliators did not have access to the patients data for both groups. Results: The frequencies for PTF type I, II and III respectively in tinnitus patients were 23.3%, 53.3% and 23.3%, and without tinnitus 6.6%, 40% and 53.33%. PTF type II was more frequent in the study group and Type III in the control group, both with 53.33%. PTF type III in the control group presented a statistically higher frequency with p = 0.039. In the study group, evaluating only ears with tinnitus, types I and II had a frequency of 72.22% and type III 27.78% (p = 0.55), however, considering the ears without the complaint, Type I and II presented a frequency of 83.33% and type III 16.67% (p = 0.021). As to the length in the study group, the values found were lower in relation to the control group, where the mean was 4, 03 mm and 5.61 mm respectively with p <0.001. Hypertrophic DML, mastoid pneumatization, PTF partial ossifications and presence of gaseous contents were the alterations found in patients with tinnitus. Conclusion: From CT, it is possible to analyze the anatomy of PTF, study its dimensions and relationships with TMJ. PTF type III is one less common in tinnitus patients. PTF type I and II had high frequencies, with significant difference in relation to type III, in tinnitus patients. PTF length in patients with tinnitus was significantly lower.